#girlgaze: photography, fourth wave feminism, and social media advocacy. Issue 6 (2nd November 2017) - Looft, Ruxandra
Abstract: The Girlgaze website was founded by television personality Amanda de Cadenet in 2016, as a social media project seeking female photographers to fund, promote and exhibit. The project lauds itself for offering girls from around the world an entry into a traditionally male-dominated profession and providing a platform where female artists can share works created through the lens of a 'girlgaze'. This article positions the Girlgaze project within the discourses of fourth wave feminism and explores how Girlgaze challenges a male-dominated industry. It also raises the questions of whose gaze we are seeing and whose world is being privileged in the production of these virtual image galleries. A closer look at the Girlgaze project, its incentives and structures raises essential questions about self-representation, social media advocacy and photography as a medium to convey any sort of truth about the world.